2015
DOI: 10.1038/srep11439
|View full text |Cite
|
Sign up to set email alerts
|

Carbon accumulation in arid croplands of northwest China: pedogenic carbonate exceeding organic carbon

Abstract: Soil carbonate (SIC) exceeds organic carbon (SOC) greatly in arid lands, thus may be important for carbon sequestration. However, field data for quantifying carbonate accumulation have been lacking. This study aims to improve our understanding of SIC dynamics and its role in carbon sequestration. We analyzed two datasets of SOC and SIC and their 13C compositions , one with over 100 soil samples collected recently from various land uses in the Yanqi Basin, Xinjiang, and the other with 18 archived soil samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
75
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 41 publications
12
75
1
3
Order By: Relevance
“…also found that the slope reached 1.9 (over 0–100 cm) in Yanqi Basin’s cropland that had access to groundwater (containing high level of Ca 2+ /Mg 2+ )15. These findings imply that increasing SOC in alkaline soil can lead to an increase of SIC in subsoil if there is no limitations of calcium (and magnesium)7.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…also found that the slope reached 1.9 (over 0–100 cm) in Yanqi Basin’s cropland that had access to groundwater (containing high level of Ca 2+ /Mg 2+ )15. These findings imply that increasing SOC in alkaline soil can lead to an increase of SIC in subsoil if there is no limitations of calcium (and magnesium)7.…”
Section: Discussionmentioning
confidence: 75%
“…On the other hand, a positive relationship between SIC and SOC was found in the Badan Jaran Desert, Gansu (over 0–30 cm)16 and in the Yanqi Basin, Xinjiang (over 0–100 cm)8. The negative relationship may only exist in surface layer where CO 2 production is high due to root respiration and decomposition of SOC, which creates acidic conditions, thus leads to dissolution of soil carbonate; the positive relationship may be more common in high pH soils and without Ca/Mg limitation7.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Nevski), were responsible for terrestrial plant's contribution. Based on our recent studies conducted in the Yanqi Basin (Wang et al, 2015;Zhang, 2013), C : N ratio was 22.1 ± 9.9 and 10 ± 1.8, and δ 13 C org value was −26.4 ± 1.2 and −23.6 ± 1.3 ‰ for the native plants and surface soils around the lake, respectively. We used the values as the end-members for the mixing model.…”
Section: Calculations Of Toc Sourcesmentioning
confidence: 99%